Nepal : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1999)
This paper reviews economic developments in Nepal during 1996-98. During 1997-98, the authorities maintained broad macroeconomic stability and there was an improvement in the external position. However, real GDP growth slowed to below 2 percent in 1997/98 (fiscal year ending July 15) and, after remaining in single digits over the last several years, the 12-month inflation rate accelerated, as food prices jumped owing to temporary agricultural supply factors. Aided by the strong exports in the region and continued generous donor financing, gross official reserves increased in 1997/98 to more than USD 700 million.